2001
DOI: 10.1186/1471-2253-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mivacurium 200 and 250 μg/kg in infants during isoflurane anesthesia: a randomized controlled trial [ISRCTN07742712]

Abstract: Background: Infants usually respond differently to a neuromuscular relaxant compared to children or adults. Isoflurane is commonly used as an anesthetic gas in infants. In an RCT design, we investigated whether a dose of mivacurium 250 µg/kg results in faster onset of action than 200 µg/kg in infants under isoflurane anesthesia. Spontaneous recovery times and cardiovascular response were also evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Electronic searches yielded 6345 potentially relevant trials, of which 71 (48 RCTs and 23 CCTs) eligible research papers (Figure 1 and Table S1) were identified, encompassing 4319 in the large majority ASA I‐II pediatric participants in 232 study arms 43–112 . We incorporated three RCTs that enrolled only a few ASA III patients 62,64,83 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Electronic searches yielded 6345 potentially relevant trials, of which 71 (48 RCTs and 23 CCTs) eligible research papers (Figure 1 and Table S1) were identified, encompassing 4319 in the large majority ASA I‐II pediatric participants in 232 study arms 43–112 . We incorporated three RCTs that enrolled only a few ASA III patients 62,64,83 .…”
Section: Resultsmentioning
confidence: 99%
“…Considering the risk of bias assessments, ROBINS‐I for CCTs 28 and RoB‐2 for RCTs, 29 (Figures S3 and S4) only 10/71 (14.1%) of the included trials 45,49–52,70,77,86,89,99 calculated the sample sizes required before starting the investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously used TOF-Guard to study the time course of the effect of mivacurium. 18 Time to onset of action after mivacurium 250 µg/kg ranged approximately 1 to 5 minutes. This is enough time to obtain multiple data of the onset of action, and therefore modeling will result in being less unbiased and more precise.…”
Section: Discussionmentioning
confidence: 99%